Failure analysis of a buried large-diameter prestressed concrete cylinder pipeline subjected to strike-slip fault displacement. (March 2022) - Li, Haizhen; Feng, Xin; Zhao, Lin
Highlights: The damage and mechanical response of pipe barrel and pipe joint are analyzed. Major failure types are material damage to pipe barrel and joint leakage. Damage process of PCCP pipeline under strike-slip fault displacement is summarized. Abstract: In this paper, the structural responses and failure analysis of a buried prestressed concrete cylinder pipeline (PCCP) subjected to strike-slip fault displacement are numerically investigated considering soil-pipe interactions. ABAQUS software was used to build a detailed pipeline model based on the optimal model length. The structural response and damage failure performance of the pipe barrels and joints were analyzed and discussed. The results showed that the main type of damage to the PCCP was damage failure in each layer of the pipe barrel caused by axial forces, pull-out leakage of the joints caused by the relative rotation angle, and compression and stacking. With increasing fault displacement, the scope and extent of pipeline damage expanded, and the pipes gradually reached the limit states. This study focused on a large-diameter PCCP to predict pipeline damage under the condition of strike-slip faults crossing the middle of a pipe barrel, and the findings of this research contribute to understanding the failure modes, damage process and disaster evaluation of PCCPs subjected to strike-slip faults.